2012
DOI: 10.1159/000339088
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Fingernail Fluoride Concentration as a Predictor of Risk for Dental Fluorosis

Abstract: The aim of this study was to validate the use of fingernail fluoride concentrations at ages 2–7 years as predictors of the risk for developing dental fluorosis in the permanent dentition. Fifty-six children of both genders (10–15 years of age) had their incisors and premolars examined for dental fluorosis using the Thylstrup-Fejerskov index. Fingernail fluoride concentrations were obtained from previous studies when children were 2–7 years of age. Data were analyzed by unpaired t test, ANOVA, and Fisher’s exac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
2
21
2
Order By: Relevance
“…Because we found no difference among groups, the statistical difference found in the fluoride concentration in nails can be attributed to the toothpastes that were used. Moreover, the water consumed showed lower mean fluoride concentrations than those found in other studies . The low fluoride concentration found in diet can be partially explained by its low concentration in water; volunteers consumed more mineral water (72%) with low fluoride concentrations.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Because we found no difference among groups, the statistical difference found in the fluoride concentration in nails can be attributed to the toothpastes that were used. Moreover, the water consumed showed lower mean fluoride concentrations than those found in other studies . The low fluoride concentration found in diet can be partially explained by its low concentration in water; volunteers consumed more mineral water (72%) with low fluoride concentrations.…”
Section: Discussionmentioning
confidence: 51%
“…Currently, nails are one of the most studied biomarkers of fluoride exposure. . Because there is a trend toward the use of low‐fluoride‐concentration toothpastes for children during the critical period of fluorosis development , in this longitudinal study, we evaluated the fluoride concentration in the nails of children considered at risk for fluorosis when 1100 μg F/g, 500 μg F/g with TMP, or 500 μg F/g with CaGP toothpastes were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study documented the validity of fingernail fluoride concentrations at age 2-7 years as a biomarker for dental fluorosis of the permanent teeth at age 10-15 years. 95 …”
Section: Monitoring Implementation Of the New Recommendationmentioning
confidence: 99%
“…Urinary fluoride excretion among the children was low, being well below the provisional standards for urinary fluoride excretion of 360-480 lg/ day for optimal fluoride usage by 3-5-year-olds (41). Measurement of fluoride level in toe/fingernails may be an alternative approach to assessing fluoride ingestion (42), as it has recently been shown that finger nail fluoride levels lower than 2 ppm are associated with reduced risk of fluorosis (43). Furthermore, the fluoride/creatinine ratio of 0.49-0.60 obtained in the present study was much below values obtained in optimally or near optimally fluoridated communities in different parts of the world: 1.49 reported by Zohouri et al (26) in the United Kingdom for children aged 1-3 years, 1.51 by Kertesz et al (33) for 8-13-year-olds in Hungary, and 1 by Szekely (44) for children aged 3-7 years in Romania.…”
Section: Discussionmentioning
confidence: 99%